Adaptive delay control for synchronous rectification phase‐shifted full bridge converter with GaN HEMT. Issue 23 (1st November 2017) - Joo, D.M.; Byun, J.E.; Lee, B.K.; Kim, J.S.
Abstract : An adaptive delay control method for a phase‐shifted full bridge converter with a synchronous rectifier is presented. With this control, the delay time between primary and secondary switches can be optimised to reduce dead time, according to output power. Moreover, due to the poor third quadrant conduction of gallium nitride (GaN) high‐electron‐mobility transistors (HEMTs), the dead time needs to be optimised to utilise the benefits of a GaN HEMT. The experimental results with a 500 W prototype show that the efficiency can be improved by 0.7% with the proposed control.